Transit bus technician test (Thomson Delmar Learning, 2006)
Prepare to take and pass the new ASE transit bus certification exam on Diesel Engines with help from this total test preparation package! Coverage begins with a brief history of ASE from its inception to the present, including a detailed description of the significance of ASE. Next, technicians receive the key information and strategies they need to take and pass this ASE exam. Realistic sample questions that reflect those actually featured on the ASE Diesel Engines exam follow, as well as up-to-date task lists and an overview of transit bus diesel engine systems. Coverage concludes with a sample ASE exam and additional test questions for further practice.